Enterotoxic Staphylococcus aureus in creamy sweets sold in bakeries in the city of S. Paulo, Brazil - Iaria, Sebastião Timo (Revista de Saúde Pública, 1981)
One hundred samples of creamy sweets were collected from 40 bakeries in the city of S. Paulo (Brazil), for the determination of Staphylococcus aureus counts per gram of food. After morphological and biochemical identification, phagetyping was performed and production of enterotoxin verified. Of the samples collected 38.0% were positive for Staphylococcus aureus. These samples came from 21 (52.5%) of the 40 bakeries. Of those positive, 7.0% were positive for enterotoxin, 5.0% for type C, 1.0% type B, and 1.0% type D. Of the 76 strains of Staphylococcus aureus isolated, 39 (51.5%) could not be classified according to known phagetypes. Of the remainder, those lysed by group I phages alone or associated to other groups predominated (21.2% and 35.5% respectively). Strains not classified under known phagetypes were isolated from 76.2% of positive establishments.